A-1 : Belgische Kunst in Zottegems Privébezit. - Ford-Centrum, Leeuwergem (Leeuwergem : Ford - Centrum, 1970)
Bertrand, Gaston ; Boulenger, Hippolyte ; Claus, Hugo ; Cockx, Philibert ; Delvaux, Paul ; Dooms, Vic ; Ensor, James ; Gailliard, Jean Jacques ; Godderis, Jack ; D'Have, Camille ; Lacasse, Joseph ; etc.
A-1 : Belgische Kunst in Zottegems Privébezit, Ford-Centrum, Leeuwergem, van 5 tot 15 juni 1970
boek